DETERMINAN KINERJA KEUANGAN INDUSTRI MIKRO DAN KECIL (IMK) KULINER DI KECAMATAN MAJENANG, CILACAP - Evi Saehtika; Heris Kencana; Anisa Fatmawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Many culinary Micro and Small Enterprises (MSMEs) in Majenang District, Cilacap Regency, still struggle to separate personal and business finances, and limited access to formal financial services can increase the risk of business failure. This study aims to identify factors influencing the financial performance of culinary MSMEs in the region. The study used a quantitative approach by distributing questionnaires to 100 culinary MSME respondents randomly selected from 585 businesses in February 2026. Data were analyzed using multiple linear regression to examine the relationships between variables determining financial performance using SPSS version 25. The results showed that financial literacy, financial management, working capital, and education level had a significant positive effect on financial performance. Conversely, financial inclusion and e-commerce had a significant negative effect. Meanwhile, digital literacy and the age of the entrepreneur had no effect. These findings indicate that improving the financial performance of culinary MSMEs requires not only access but also adequate business management capacity. This study recommends strengthening financial literacy and management, providing assistance in accessing formal finance, optimizing working capital, and improving education and training to enable culinary MSMEs to grow more sustainably and support the local economy.